How Terrorism Explains Capital Flight from Africa - Uchenna Efobi; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
We assess the effects of terrorism on capital flight in a panel of 29 African countries for which data is available for the period 1987-2008. The terrorism dynamics entail domestic, transnational, unclear and total terrorisms. The empirical evidence is based on Generalised Method of Moments (GMM) with forward orthogonal deviations and Quantile regressions (QR). The following findings are established. First, for GMM, domestic, unclear and total terrorisms consistently increase capital flight, with the magnitude relative higher from unclear terrorism. Second, for QR: (i) the effect of transnational terrorism is now positively significant in the top quantiles (0.75th and 0.90th) of the capital flight distribution, (ii) domestic and total terrorisms are also significant in the top quantiles and (iii) unclear terrorism is significant in the 0.10th and 0.75th quantiles. Policy implications are discussed.
Keywords: C50; D74; F23; N40; O55; 330; Capital flight; terrorism; Africa